Serum Krebs von den Lungen-6 before treatment predicts the prognosis of lung cancer in Asian populations: a systematic review and meta-analysis - Huang, Hong; Fu, Liangyu; Feng, Chenye; Zhou, Jiawei; Xu, Jiahuan; Sun, Jianjun; Pan, Ying; Kong, Delei; Wang, Wei (Frontiers in Immunology, 2025)
BackgroundUp until now, no clear consensus has been reached on the role of serum Krebs von den Lungen-6 (KL-6) levels in predicting survival in patients with lung cancer. This meta-analysis aimed to assess the prognostic value of serum KL-6 levels before treatment in lung cancer.MethodsPubMed, Web of Science, Embase, and Cochrane Library were searched for relevant studies from inception to June 23, 2025. This study was registered with PROSPERO (CRD42024568549).ResultsThirteen studies involving 1,723 patients were included in this meta-analysis. High serum KL-6 levels before treatment were associated with shorter progression-free survival (hazard ratio [HR] 1.89, 95% confidence intervals [95% CI]: 1.46–2.44, P<0.001; heterogeneity: I²=6.5%, P = 0.37) and overall survival (OS) (HR 1.76, 95% CI: 1.37–2.26, P<0.001; heterogeneity: I²=51.9%, P = 0.023). Subgroup analysis revealed the significant value of elevated KL-6 level for predicting OS of patients with lung cancer without interstitial lung disease (ILD) but not for those with ILD. The pooled results indicated that OS and progression-free survival were shortened when serum KL-6 level exceeded 500 U/mL. The serum KL-6 level determined using electrochemiluminescence immunoassay had a greater predictive value for OS than that determined using enzyme-linked immunosorbent assay in this study.ConclusionElevated serum KL-6 levels (>500 U/mL) before treatment represent a biomarker for poor prognosis of lung cancer for Asian patients without ILD. However, in patients with pre-existing ILD, these elevated levels are more likely to indicate the severity and activity of the underlying fibrotic lung disease rather than providing independent prognostic information about the cancer itself. Electrochemiluminescence immunoassay was recommended for determining the serum KL-6 level.Systematic review registrationhttps://www.crd.york.ac.uk/PROSPERO/, identifier CRD42024568549.